Robot behavior debugger for non-expert users in convenience stores using behavior trees. (17th September 2022) - Tulathum, Pattaraporn; Usawalertkamol, Bunyapon; Garcia Ricardez, Gustavo Alfonso; Takamatsu, Jun; Ogasawara, Tsukasa; Matsumoto, Kenichi
ABSTRACT: As the problematic consequence of an aging society, with increasing labor shortage, there is a need for service robots to efficiently support the works in many places such as convenience stores. However, it is difficult to program a robot behavior and meet the needs of the shop staff (i.e. non-expert users who lack of knowledge and experience in robot programming). Hence, there is the need for a system to help non-expert users to identify and fix the issues within the robot behaviors. This paper proposes a Behavior Tree-based robot behavior creation system for non-expert users with four debugging features and a simulator. Non-expert users can use drag-and-drop composition to create the robot behavior program. Moreover,  our debugger allows non-expert users to use breakpoints, log node status, monitor node execution, show robot status variables,  and also can visually verify the robot behaviors via a simulator. We evaluate the effectiveness of our debugging system with 14 non-expert users by asking them to solve three tasks (i.e. creating and fixing Behavior Trees) from the given convenience store scenario. The experimental results show that more than 70% of non-expert users can utilize our debugging features to finish all the tasks. Additionally, our system usability has a high marginal level from the subjects' perspective according to the System Usability Scale (SUS). GRAPHICAL ABSTRACT: UF0001